Advance care planning for older people: The influence of ethnicity, religiosity, spirituality and health literacy. (November 2019) - de Vries, Kay; Banister, Elizabeth; Dening, Karen Harrison; Ochieng, Bertha
In this discussion paper we consider the influence of ethnicity, religiosity, spirituality and health literacy on Advance Care Planning for older people. Older people from cultural and ethnic minorities have low access to palliative or end-of-life care and there is poor uptake of advance care planning by this group across a number of countries where advance care planning is promoted. For many, religiosity, spirituality and health literacy are significant factors that influence how they make end-of-life decisions. Health literacy issues have been identified as one of the main reasons for a communication gaps between physicians and their patients in discussing end-of-life care, where poor health literacy, particularly specific difficulty with written and oral communication often limits their understanding of clinical terms such as diagnoses and prognoses. This then contributes to health inequalities given it impacts on their ability to use their moral agency to make appropriate decisions about end-of-life care and complete their Advance Care Plans. Currently, strategies to promote advance care planning seem to overlook engagement with religious communities. Consequently, policy makers, nurses, medical professions, social workers and even educators continue to shape advance care planning programmes within the context of a medical model. The ethical principle of justice is a useful approach to responding to inequities and to promote older peoples' ability to enact moral agency in making such decisions.